1999
DOI: 10.1272/jnms.66.41
|View full text |Cite
|
Sign up to set email alerts
|

Fibroin allergy. IgE mediated hypersensitivity to silk suture materials.

Abstract: Delayed-type hypersensitivity with granulomatous lesions to silk sutures is rather rare. Yet, braided silk sutures often act as a non-immunologic foreign-body and cause a granulomatous inflammatory reaction years after surgery. We report here a case of recurrent granulomas with remarkable infiltration of eosinophils that may have resulted from an IgE-mediated hypersensitivity reaction to silk fibroin, a component of the braided silk suture. Under normal circumstances exposure to fibroin is rather rare. Therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
0
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 98 publications
(54 citation statements)
references
References 10 publications
0
49
0
2
Order By: Relevance
“…In addition, in the preparation of this review no references were found in the literature that implicated black braided silk in inducing hypersensitivity and allergic reactions. Kurosaki et al [30] concluded that the hypersensitivity in their single case may have been the result of patient sensitization to silk from a prior surgical procedure 7 years earlier. The type of silk used in this earlier exposure was unknown (e.g., virgin vs. black braided).…”
Section: In Vivo Biocompatibility Of Virgin Silkmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, in the preparation of this review no references were found in the literature that implicated black braided silk in inducing hypersensitivity and allergic reactions. Kurosaki et al [30] concluded that the hypersensitivity in their single case may have been the result of patient sensitization to silk from a prior surgical procedure 7 years earlier. The type of silk used in this earlier exposure was unknown (e.g., virgin vs. black braided).…”
Section: In Vivo Biocompatibility Of Virgin Silkmentioning
confidence: 99%
“…Virgin silk, like most proteins, is a potential allergen [28,29] causing a Type I allergic response in some cases [30]. Delayed allergic responses to silk (an average of 10 months after initial exposure) induced some patient complications including asthma and specific upregulation in IgE levels [29,31].…”
Section: In Vivo Biocompatibility Of Virgin Silkmentioning
confidence: 99%
See 3 more Smart Citations